Simultaneously improving flame retardancy, water and acid resistance of ethylene vinyl acetate copolymer by introducing magnesium hydroxide/red phosphorus co-microcapsule and carbon nanotube. (January 2020) - Liu, Jichun; He, Yunpeng; Chang, Haibo; Guo, Yingbin; Li, Hang; Pan, Bingli
Abstract: In this work, a co-microcapsule of magnesium hydroxide (MH) and red phosphorus (RP) (denoted as M[MH&RP]) was synthesized using 4, 4′-diphenylmethane diisocyanate and melamine via one-step in-situ surface polymerization, which was subsequently introduced into ethylene vinyl acetate copolymer (EVA) as a flame retardant. The results indicate that the core-shell structured co-microcapsule displays increased thermal and thermo-oxidative stability as well as better dispersion in EVA. Flame retardancy of the EVA/M[MH&RP] composite improves significantly in comparison with the EVA/MH/RP composite due to formation of continuous and compact char layer on the surface of the composite. Moreover, this flame-retardant composite exhibits excellent water and acid resistance. The addition of a small amount of multi-walled carbon nanotube (MWCNT) further increases flame retardancy of the EVA/M[MH&RP] composite considerably and the flame-retardant EVA/M[MH&RP]/MWCNT composite has good mechanical flexibility and electrical insulation. This work has provided a simple method to prepare multi-functional flame-retardant EVA composite. Highlights: Co-microencapsulation of MH/RP mixture can improve its flame-retardant efficiency in EVA significantly. The flame-retardant EVA/M[MH&RP] composite exhibits excellent water and acid resistance. The introduction of a small amount of MWCNT can increases flame retardancy of the composite remarkably.